PERBEDAAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL PEMBELAJARAN LEARNING CYCLE 5 FASE DAN MODEL PEMBELAJARAN INQUIRY LEARNING PADA MATA PELAJARAN IPA DI KELAS IV DI GUGUS III KECAMATAN SITUBONDO TAHUN 2021/2022 - Febrianto, Mory Victor; Setiawan, Gustilas Ade; Zahro, Nur Holifatuz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Difference of Student critical thinking skills by using the learning cycle 5 fase and inquiry learning In science at Fourth Grade In the third cluster at Situbondo 2017/2018 Academic Year. Thesis. Primary School Teacher Department. Faculty of Teacher Training and Education.  Abdurachman Saleh Situbondo University. The aim of this study is to determine whether there is significant differences in the results of  Science between students who follow the learning cycle 5 fase with the inquiry lerning in IV class. This research was conducted in SDN 5 Dawuhan at Fourth Grade with 33 students by using the learning cycle 5 fase and in SDN 3 Dawuhan with 32 students by using the inquiry learning. The type of this research is quantitative research. While the data analysis is Normality Test, Homogeneity Test and Hypothesis Test. From the results of the calculation of t-test by using t-test obtained Tcount= 8,608 as well as Ttable (at significant level (α) = 0.05 with degrees of freedom 58) = 2,002. because Tcount > Ttable, then Ho was rejected and Ha accepted, based on the results of testing the hypotheses, it could be concluded that the learning cycle 5 fase had differences of student critical thinking skills by the inquiry learning on Science, although it uses the Standard Competence and Basic Competence in the same as the source and medium of learning.